Factionalization of the Majelis Mujahidin Indonesia: Transformation of the Leadership of a Terror Organization into a Political Organization - Yassirly Amrona Rosyada; Alvin Noor Sahab Rizal; Muhammad Noor Sulaiman Syah (Journal of Islamic History, 2025)
This study analyzes the Majelis Mujahidin mass organization where in its development there were internal conflicts that caused several internal factions and a shift in leadership figures. Based on the support and study of the theory of factionalism, identity politics, and leadership, this thesis aims to find out some of the factions in the Majelis Mujahidin and the shift in the area of da'wah from Yogyakarta to West Sumatera. This study uses two types of data sources, namely primary data sourced from the field, observation and in-depth interviews. While secondary data is the type of data that comes from scientific works such as books, articles, journals and others related to the context of this research, especially about factionalism and identity politics of the Majelis Mujahidin. While the method in this research is a qualitative-descriptive method that uses a socio-political approach. The results of the study revealed that the Majelis Mujahidin had several factions. The first is the Abu Bakar Ba'asyir faction with a jihadist da'wah style. The two factions of Muhammad Talib where the Majelis Mujahidin in their preaching emphasize study through knowledge. The three factions Irfianda Abidin and Jel Fathullah with political missions. The emergence of Jel Fathullah and Irfianda Abidin advancing in the realm of Indonesian politics is quite surprising for Indonesian Islamic organizations. Both are known to be in the central management structure of the Majelis Mujahidin. As a result, the Majelis Mujahidin, which is well-known as an organization that challenges the democratic system, raises its figures to participate in the contestation in a system that it considers kufr. The emergence of political factions in the Majelis Mujahidin certainly shows that their existence is quite massive to this day. REFERENCES Abdul Aziz, “Gerakan Politik Penegakan Syari’at Islam Di Era Reformasi Kasus Majelis Mujahidin Indonesia 2000-2005”, dalam Jurnal Review Politik 2, no. 2, 2012. Abi Chusna, “Konsep Jihad Hizbut Tahrir Indonesia (HTI) dan Majelis Mujahidin Indonesia (MMI): Studi Perbandingan,” Disertasi UIN Sunan Ampel Surabaya, 2014. Ali Sodiqin, “Genealogi Gerakan Penegakan Syari’at Islam Di Indonesia”, dalam Al-Mazahib: Jurnal Pemikiran Hukum 3, no. 1, 2015. Asran Jalal, A. J. "Organisasi Salafi di Indonesia: Studi Ideologi dan Pemikiran Politik Front Pembela Islam, Majelis Mujahidin Indonesia dan Hizbut Tahrir Indonesia." (2019). Azyumardi Azra, “Islam di Tengah Arus Transisi Menuju Demokrasi” dalam Abdul Mu’in (ed.), Islam di Tengah Arus Transisi, Jakarta: Kompas, 2000. Boyer, Ming M., Loes Aaldering, and Sophie Lecheler. "Motivated reasoning in identity politics: Group status as a moderator of political motivations." Political Studies 70.2 (2022): 385-401. Budiatri Aisah Putri, et al. Menimbang Demokrasi Dua Dekade Reformasi, Jakarta: Yayasan Pustaka Obor Indonesia, 2019. Chaq, Moh Dliya'ul. "Pemikiran Hukum Gerakan Islam Radikal Studi atas Pemikiran Hukum dan Potensi Konflik Sosial Keagamaan Majelis Mujâhidin Indonesia (MMI) dan Jamâ’ah Anshârut Tauh? id (JAT." Tafáqquh: Jurnal Penelitian dan Kajian Keislaman 1.1 (2013): 16-42. Endang Turumudi dan Riza Sihbudi, dkk., Islam dan Radikalisme di Indonesia, Jakarta: LIPI Press, 2005. Guillermo O Donnel & Philippe C. Schimetter, Transisi Menuju Demokrasi, terj. Hartono, Jakarta: LP3ES, 1993. Haedar Nashir, “Gerakan Islam Syariat: Reproduksi Salafiyah Ideologis di Indonesia”, dalam Jurnal Maarif: Arus Pemikiran Islam dan Sosial 1, no. 2, 2006. Hermanto, Hermanto. "Kritik Wacana Tafsir Tentang Terorisme." Sosio Akademika 12.2 (2023): 32-53. Hiariej, Eric. "Aksi dan identitas kolektif gerakan Islam radikal di Indonesia." Jurnal Ilmu sosial dan Ilmu politik 14.2 (2010): 131-168. Knowles, Eric D., Linda R. Tropp, and Mao Mogami. "When White Americans see “non-Whites” as a group: Belief in minority collusion and support for White identity politics." Group Processes & Intergroup Relations 25.3 (2022): 768-790. Kurniawan, Anwar, and Ahmad Aminuddin. "Muhammad Thalib, Majelis Mujahidin Indonesia, Dan Tafsir Ayat-Ayat Penegakan Syariat Islam Di Indonesia." Teosofi: Jurnal Tasawuf dan Pemikiran Islam 8.1 (2018): 113-143. Thalibdalam khutbah Iftitah saat pembukaan KongresMujahidin ke-IV di Masjid az-Zikra, Sentul, Bogor, Jawa Barat, 2013. Mario Diani, “The Concept of Social Movement”, dalam Kate Nash (ed), Readings in Contemporary Political Sociology, Malden-Massachutes: Blackwell Publishers, 2000. Mohamad Yahya. “Peneguhan Identitas dan Ideologi Majelis Mujahidin Melalui Terjemah Al-Qur’an”, dalam RELIGIA 21, no. 2, 2018. Muhammad Thalib, Tafsir Al-Fatihah dan Juz ‘Amma, Yogyakarta: MU Media, 2010. Muntoha, Otonomi Daerah dan Perkembangan Peraturan Daerah Bernuansa Syari’ah, Yogyakarta: Safiria Insania Press, 2010. Muthoharoh, Intan, Bukhori Abdul Somad, and Masruchin Masruchin. "Abu Bakar Ba'asyir Dan Perannya Dalam Majelis Mujahidin Indonesia (MMI)." Ta'lim 5.2 (2023): 1-16. Prasetyo, Budi. "Toleransi Majelis Mujahidin Indonesia Dalam Keberagamaan, Sosial, Budaya Dan Politik." (2013). Qiuyun, Guo, et al. "Leader humility and employee organizational deviance: the role of sense of power and organizational identification." Leadership & organization development journal 41.3 (2020): 463-479. Rancière, Jacques. "Politics, identification and subjectivization." Identity Trumps Socialism. Routledge, 2023. 35-40. Rosidin, Rosidin. "Relasi Sosial Majelis Mujahidin Dalam Konstelasi Kebangsaan." Al-Qalam 22.1 (2016): 105-116. Sholehuddin, Moh. "Ideologi Religio-Politik Gerakan Salafi Laskar Jihad Indonesia." JRP (Jurnal Review Politik) 3.1 (2013): 47-68. SK Majelis Mujahidin oleh peserta Mudzakarah Nasional Yogyakarta, 10 Safar 1437/22. November 2015. lajnah tanfidziyah Majelis Mujahidin. Wahab, Abdul Jamil. "Majelis Mujahidin Menuju Indonesia Bersyariat." Harmoni 22.1 (2023): 234-247. Zaki Mubarak, Genealogi Islam Radikal di Indonesia, Jakarta: LP3ES, 2008. Zubaidi, Ahmad. "Ahlussunah Wal Jamaah's Political Practices In Post-Reform Indonesia." Al-Risalah: Jurnal Studi Agama Dan Pemikiran Islam 12.2 (2021): 273-296. Zuhri, Achmad Muhibin. Islam moderat: konsep dan aktualisasinya dalam dinamika gerakan Islam di Indonesia. Vol. 1. Academia Publication, 2022.